Optimal crashworthiness design of a spot-welded thin-walled hat section - Xiang, Yujiang; Wang, Qian; Fan, Zijie; Fang, Hongbing (Finite elements in analysis and design, 2006)
In automotive industry, crashworthiness design is of special interest to ensure passengers safety and reduce vehicle costs. Thin-walled beams are the main energy absorbing structures in frontal and real collisions; therefore, it is important to investigate their energy-absorption and optimize their performance. For crashworthiness designs of thin-walled sections, much attention has been given to the size and shape designs of the cross-section, while limited study has been performed to incorporate spot-weld modelling and their numbers as design parameters in crashworthiness optimization. The spacing of spot-welds has a strong effect on crashworthiness performance, because it can change a single complete folding length. This study focuses on the optimal crashworthiness design of a spot-welded thin-walled hat section subject to an axial crushing force. Based on comparisons to experimental data, an appropriate spot-weld model is selected and used in numerical simulations. The mass of the beam is optimized subjected to constraints of required mean crushing force and bending stiffness. A “Two-step RSM-Enumeration” algorithm is employed to efficiently solve this optimization problem of mixed-type variables.